Nylon composite material as well as preparation method and application thereof
By adding high molecular weight brominated polystyrene, polyphenylene ether resin and polyether polyamide elastomer to nylon composite materials, the problem of insufficient weld line strength of brominated flame-retardant nylon composite materials is solved and the material strength is improved. Significantly improved applicability to complex structures.
Patent Information
- Application Number
- CN202411540873.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The prior art is difficult to effectively improve the welding wire strength of bromine flame-retardant nylon composite materials, especially in complex structures, the material strength at the welding wire position is weak and defects are easily formed.
By adding high molecular weight brominated polystyrene, polyphenylene ether resin and polyether polyamide elastomer to nylon composite materials, the material ratio and preparation process are optimized to improve the compatibility and strength of the material.
It significantly increases the weld line strength of nylon composite materials, improves the mechanical properties and stress cracking characteristics of the material, and is suitable for parts with complex structures.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to a nylon composite material and a preparation method and application thereof. Background Art
[0002] Nylon resin has excellent mechanical properties, barrier properties, heat resistance, wear resistance, chemical corrosion resistance and other comprehensive properties. Its composite materials are widely used in machinery manufacturing, industrial connectors, power tools, electronic appliances, transportation and other fields. In many application scenarios, the demand for flame retardant materials is getting higher and higher. Environmentally friendly bromine flame retardant system is still the largest and most widely used product in flame retardant nylon products due to its high flame retardant efficiency, high glow wire characteristics, no frost, easy coloring, excellent mechanical properties and other characteristics.
[0003] The weld line problem of injection molded products has always been a difficult problem in the industry, especially for products with complex structures such as round holes, squares, irregular polygons, etc. Whether it is single-point or multi-point injection molding, weld lines are easily formed at the confluence of different melts, which has an adverse effect on the product. Because the material strength at the weld line is weak, it is easy to form defects, and material failure problems are prone to occur during product use. Especially for metal insert products, the thermal expansion coefficients of polymer materials and metal materials are different, and internal stress will be generated at the weld line junction, which is more likely to form defects.
[0004] The existing technology mainly improves the weld mark strength by the following methods: CN 110733159A uses a special injection mold to obtain a spray-free plastic product without weld line defects. This method places extremely high requirements on the injection mold and supporting equipment, and requires the mold to be heated and cooled extremely quickly. General products cannot meet this special mold requirement.
[0005] CN 105419291 B uses a composite of a styrene-acrylonitrile-glycidyl methacrylate random copolymer and a peroxide-grafted styrene-acrylonitrile copolymer as a compatibilizer to prepare a PC / ABS alloy with excellent weld line appearance and high strength; CN 109535682 A uses an ethylene copolymer compatibilizer to improve the weld line strength of a polyethylene / polycarbonate alloy. Such solutions are more commonly used in alloy systems.
[0006] However, for the brominated flame retardant system, especially the brominated polystyrene flame retardant (BPS flame retardant) with good thermal stability, the base material of BPS flame retardant is styrene resin, which is a non-crystalline, non-polar polymer material. It is not compatible with crystalline nylon resin containing amide bond polar groups. In addition, the difference in molecular weight of flame retardants leads to low weld line strength of BPS brominated flame retardant nylon composite materials.
[0007] For the reinforcement system, the glass fiber is easy to arrange along the flow direction to form a certain orientation during the injection molding process. However, when the melt encounters obstacles during the flow process, the arrangement direction of the glass fiber will change and be arranged perpendicular to the flow direction. The strength of the material in this direction will decrease. When the melt encounters obstacles and is divided into two or more streams and then reunited, the front end of the melt cools faster, and the fusion effect at the weld line is worse, resulting in a decrease in strength. Summary of the invention
[0008] The object of the present invention is to overcome the above technical defects and provide a flame retardant nylon composite material with high weld mark strength.
[0009] The present invention is achieved through the following technical solutions: A nylon composite material, comprising the following components in parts by weight: Nylon resin 50-80 parts; 10-20 parts of polyphenylene ether resin; 2-10 parts of polyether polyamide elastomer; 15-25 parts of brominated polystyrene; 3-8 parts of flame retardant synergist; The weight average molecular weight of the brominated polystyrene is 180,000-300,000; The Shore hardness of polyether polyamide elastomer is 38D-70D. Refer to ISO 868 test and record the value after 15 seconds.
[0010] The weight average molecular weight of the polyphenylene ether resin of the present invention is in the range of 10000-30000, preferably, the weight average molecular weight of the polyphenylene ether resin is in the range of 14000-25000, and more preferably, the weight average molecular weight of the polyphenylene ether resin is in the range of 17000-21000.
[0011] The monomer of the polyphenylene ether resin of the present invention is 2,6-dimethylphenol.
[0012] The weight average molecular weight of the polyphenylene ether resin is measured by gel permeation chromatography (GPC) using tetrahydrofuran as solvent.
[0013] The polyphenylene ether of the present invention is prepared by a homemade method or a commercial product, and the homemade method is as follows: a catalyst system consisting of toluene, copper chloride and diethylamine is sequentially added to a reactor, and a toluene solution of 2,6-dimethylphenol is added dropwise under stable oxygen supply conditions, and the reaction is carried out at 15-25° C. for 10 min-120 min. The longer the reaction time, the greater the molecular weight, and the weight-average molecular weight of the material is controlled according to the reaction time. When the target molecular weight is reached, acetic acid is added to terminate the experiment, and the polymer is separated by precipitation with anhydrous ethanol, dissolved in toluene, and re-precipitated with sewage ethanol, and then dried in a vacuum oven to constant weight. Among them, the amine / copper molar ratio is preferably 30-40:1, and the molar ratio of the amount of 2,6-dimethylphenol to the copper ion is preferably 30-40:1.
[0014] Preferably, the Shore hardness of the polyether polyamide elastomer is D50-D65, and the test is performed according to ISO 868, and the value is recorded after 15 seconds.
[0015] Polyether polyamide elastomer is a thermoplastic elastomer polymerized from flexible polyether and hard polyamide. It has a large number of ether bonds and amide bonds in its molecular structure and has good compatibility with nylon resin and polyphenylene ether resin. The higher the content of hard polyamide segment in polyether polyamide elastomer, the higher the Shore hardness.
[0016] The flame retardant synergist is selected from antimony compounds, such as at least one of antimony trioxide and sodium antimonate.
[0017] The nylon resin is selected from at least one of the polyamide resins selected from aliphatic polyamide resins, semi-aromatic polyamide resins, and polylactamide resins.
[0018] The aliphatic polyamide resin is selected from PA66, PA46, PA610, PA612, PA56, PA510, PA512, PA910, PA912, PA913, PA914, PA915, PA616, PA936, PA1010, PA1012, PA1013, PA1014, PA1210, PA1212, PA1213, PA1214, PA614, PA613, PA615, PA616 and the like.
[0019] The semi-aromatic polyamide is selected from PA MXD6, PA10T, PA10T1010, PA10T66, PA6T, PA6T66, PA9T and the like.
[0020] The polylactam is selected from PA5, PA6, PA11, PA12 and the like.
[0021] By weight, it also includes 0-40 parts of reinforcing agent, and the reinforcing agent is selected from at least one of glass fiber and mineral filler; by weight, it also includes 0-2 parts of auxiliary agent, and the auxiliary agent is selected from at least one of antioxidant, lubricant and weathering agent.
[0022] The preparation method of the nylon composite material of the invention comprises the following steps: mixing the components uniformly according to the proportion, and extruding and granulating the components through a twin-screw extruder to obtain the nylon composite material.
[0023] The invention discloses an application of nylon composite materials for preparing electronic and electrical parts, parts requiring metal inserts, and other parts with complex structures.
[0024] The present invention has the following beneficial effects: The present invention reduces the viscosity difference between the resin matrix and the flame retardant by adopting high molecular weight brominated polystyrene, thereby reducing the local single component enrichment phenomenon, especially the flame retardant enrichment, and reducing the negative impact on the mechanical strength of the composite material. By introducing PPE resin, the crystallinity of the PA material can be moderately reduced, but without losing the advantages of nylon itself such as temperature resistance, pressure solvent resistance, and high strength, the cooling rate of the weld line position is reduced, and the two melts are melted better. Further, the polyether-type polyamide elastomer having a specific ratio (characterized by Shore hardness) of flexible polyether segments and hard polyamide polymerization, while improving the toughness of the material, does not require additional interfacial compatibilizers, so that the elastomer and the nylon matrix resin and the polyphenylene ether resin can be dispersed at the molecular level, further strengthening the strength of the weld line position, and even if there is a weld line, the weld line position can maintain excellent stress cracking characteristics. Thereby greatly expanding the application of flame-retardant nylon, especially complex structure products. DETAILED DESCRIPTION
[0025] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0026] Nylon 66: PA66 EP-158, Huafeng Group Co., Ltd. Nylon 6: PA6 HY-2500A, Haiyang Technology Co., Ltd.; Nylon 66 / 6: PA66 88X, Ascend Performance Materials Co., Ltd.; The following polyphenylene ether is prepared by the following method: toluene as a solvent, a catalyst system consisting of copper chloride and diethylamine (amine / copper molar ratio of 35:1) is added to the reactor in sequence, and under stable oxygen supply conditions, a toluene solution of 2,6-dimethylphenol is added dropwise, and the molar ratio of 2,6-dimethylphenol to copper ions is 35:1. The reaction time is 10min-2h at 20°C. The longer the reaction time, the greater the molecular weight. The molecular weight of the material is controlled according to the reaction time. After a period of reaction, acetic acid is added to terminate the experiment. After the polymer is separated by precipitation with anhydrous ethanol, it is dissolved in toluene and re-precipitated with sewage ethanol, and then dried in a vacuum oven to constant weight.
[0027] Polyphenylene ether A: reaction time about 27min, weight average molecular weight 14000, homemade; Polyphenylene ether B: reaction time about 33 min, weight average molecular weight 17500, homemade; Polyphenylene ether C: reaction time about 40 min, weight average molecular weight 21000, homemade; Polyphenylene ether D: reaction time about 45 min, weight average molecular weight 24000, homemade; Polyphenylene ether E: reaction time about 20 min, weight average molecular weight 11000, homemade; Polyphenylene ether F: reaction time about 60 min, weight average molecular weight 29000, homemade; Brominated polystyrene A: BPS 7010, weight average molecular weight 190,000, Shandong Tianyi Chemical Co., Ltd. Brominated polystyrene B: XZ-6700, weight average molecular weight 240,000, Shandong Brother Chemical Co., Ltd.; Brominated polystyrene C: SAYTEX HP-5010PST, weight average molecular weight 4702, Yabao Chemical Co., Ltd.; Glass fiber: Glass fiber ECS10-03-568H, China Jushi Co., Ltd.; Antimony trioxide: S-05N, Changde Chenzhou Antimony Products Co., Ltd.; Polyether polyamide elastomer 1: Pebax® Rnew 25R53 SP 01, hardness of Shore 22D (after 15 seconds), Arkema, France; Polyether polyamide elastomer 2: Pebax® Rnew 35R53 SP 01, hardness of Shore 25D (after 15 seconds), Arkema, France; Polyether polyamide elastomer 3: PEBAX® MH 2030, hardness of Shore 40 D (after 15 seconds), Arkema, France; Polyether polyamide elastomer 4: Pebax® Rnew 40R53 SP 01, hardness of Shore 39 D (after 15 seconds), Arkema, France; Polyether polyamide elastomer 5: Pebax® Rnew 55R53 SP 01, hardness of Shore 51D (after 15 seconds), Arkema, France; Polyether polyamide elastomer 6: Pebax® Rnew 63R53 SP 01, hardness of Shore 56 D (after 15 seconds), Arkema, France; Polyether polyamide elastomer 7: Pebax® Rnew 70R53 SP 01, hardness of Shore 62D (after 15 seconds), Arkema, France; Polyether polyamide elastomer 8: Pebax® Rnew 72R53 SP 01, hardness of Shore 65 D (after 15 seconds), Arkema, France; Polyether polyamide elastomer 9: Pebax® Rnew 80R53 SP 01, hardness of Shore 67D (after 15 seconds), Arkema, France; Comparative toughening agent 1: Fusabond N493, maleic anhydride grafted low Tg ethylene copolymer, DuPont; Comparative toughening agent 2: SEBS FG1901 GT, a linear triblock copolymer of styrene and ethylene / butylene, Kraton Corporation; Comparative toughening agent 3: KT-7K, maleic anhydride grafted EPDM rubber, Shenyang Ketong Plastic Co., Ltd.; Embodiment and comparative example Preparation method of high weld mark strength flame-retardant nylon composite material: According to the ratio, the components are evenly mixed, and granulated by extrusion through a twin-screw extruder to obtain a high weld mark strength flame-retardant nylon composite material, wherein the screw barrel temperatures of the extruder are 160°C, 250°C, 260°C, 260°C, 240°C, 230°C, 230°C, 230°C, 240°C and 260°C, respectively, and the speed is set to 350rpm-450rpm.
[0028] Various test methods: (1) Weld line strength: The weld line strength is measured using an ISO 527 standard tensile test strip mold with two inlets. During the injection molding process, the melt is filled from both ends to the middle, forming a weld line in the middle. The weld line strength is measured using the ISO 527 tensile test method. The tensile rate is 10 mm / min and the unit is MPa.
[0029] (2) Flame retardant grade: The test is carried out in accordance with UL 94 standard, and the test specimen size is 125mm*13mm*1.6mm.
[0030] Table 1: Component contents and test results of high weld mark strength flame retardant nylon composite materials of Examples 1-6 Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Nylon 66 50 Nylon 6 60 60 60 60 Nylon 66 / 6 80 Polyphenylene oxide A 10 15 20 15 Polyphenylene ether B 15 Polyphenylene ether C 15 Brominated polystyrene A 15 25 Brominated polystyrene B 20 20 20 20 Polyether polyamide elastomer 3 5 2 10 4 4 4 Antimony trioxide 8 6 3 6 6 6 Fiberglass 10 10 10 Flame retardant grade V-0 V-0 V-0 V-0 V-0 V-0 Weld mark strength MPa 61 66 64 75 79 81 Table 2: Component contents and test results of high weld strength flame retardant nylon composite materials of Examples 7-9 Example 7 Example 8 Example 9 Nylon 6 60 60 60 Polyphenylene ether D 15 Polyphenylene ether E 15 Polyphenylene ether F 15 Brominated polystyrene B 20 20 20 Polyether polyamide elastomer 3 4 4 4 Antimony trioxide 6 6 6 Fiberglass 10 10 10 Flame retardant grade V-0 V-0 V-0 Weld mark strength MPa 77 73 72 It can be seen from Examples 4-9 that the weight average molecular weight of polyphenylene ether mainly affects the dispersibility and compatibility of polyphenylene ether in the resin matrix, and the weld mark strength is higher when the weight average molecular weight is within the preferred range.
[0031] Table 3: Component contents and test results of high weld strength flame retardant nylon composite materials of Examples 10-15 Example 10 Embodiment 11 Example 12 Embodiment 13 Embodiment 14 Embodiment 15 Nylon 6 60 60 60 60 60 60 Polyphenylene ether B 15 15 15 15 15 15 Brominated polystyrene B 20 20 20 20 20 20 Polyether polyamide elastomer types 4 5 6 7 8 9 Polyether polyamide elastomer content 4 4 4 4 4 4 Antimony trioxide 6 6 6 6 6 6 Fiberglass 10 10 10 10 10 10 Flame retardant grade V-0 V-0 V-0 V-0 V-0 V-0 Weld mark strength MPa 73 81 81 84 80 77 It can be seen from Examples 4 / 10-15 that the weld mark strength is higher when the Shore hardness of the polyether polyamide elastomer is preferred.
[0032] Table 4: Content of each component and test results of flame retardant nylon composite materials of comparative examples 1-6 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Nylon 6 60 60 60 60 60 60 Polyphenylene oxide A 0 5 30 15 15 15 Brominated polystyrene B 20 20 20 20 20 Brominated polystyrene C 20 Polyether polyamide elastomer 3 4 4 4 4 0 15 Antimony trioxide 6 6 6 6 6 6 Fiberglass 10 10 10 10 10 10 Flame retardant grade V-2 V-0 V-0 V-0 V-0 V-0 Weld mark strength MPa 43 47 41 38 42 45 It can be seen from Comparative Example 1 / 2 that when no polyphenylene ether is contained or the content is too low, the weld mark strength is low.
[0033] It can be seen from Comparative Example 3 that when the polyphenylene ether content is too high, the weld mark strength is low.
[0034] It can be seen from Comparative Example 4 that the conventional low molecular weight brominated polystyrene has too low weld mark strength of the composite material due to its dispersibility.
[0035] It can be seen from Comparative Examples 5 / 6 that when the content of the polyether polyamide elastomer is too high or 0, the weld mark strength is too low.
[0036] Table 5: Content of each component and test results of flame retardant nylon composite materials of comparative examples 7-11 Comparative Example 7 Comparative Example 8 Comparative Example 9 Comparative Example 10 Comparative Example 11 Nylon 6 60 60 60 60 60 Polyphenylene oxide A 15 15 15 15 15 Brominated polystyrene B 20 20 20 20 20 Polyether polyamide elastomer 1 4 Polyether polyamide elastomer 2 4 Comparative toughening agent 1 4 Comparative toughening agent 2 4 Comparative toughening agent 3 4 Antimony trioxide 6 6 6 6 6 Fiberglass 10 10 10 10 10 Flame retardant grade V-0 V-0 V-0 V-0 V-0 Weld mark strength MPa 46 50 35 37 40 It can be seen from Example 4 and Comparative Examples 7-8 that if the Shore hardness of the polyether polyamide elastomer is not within the range of the present invention, the weld mark strength of the composite material is too low.
[0037] It can be seen from Comparative Examples 9-11 that the toughening agent commonly used in nylon materials has low weld mark strength when applied to the system of the present invention.
Claims
1. A nylon composite material, characterized in that: By weight, it includes the following components: Nylon resin 50-80 parts; 10-20 parts of polyphenylene ether resin; 2-10 parts of polyether polyamide elastomer; 15-25 parts of brominated polystyrene; 3-8 parts of flame retardant synergist; The weight average molecular weight of the brominated polystyrene is 180,000-300,000; The Shore hardness of polyether polyamide elastomer is 38D-70D. Refer to ISO 868 test and record the value after 15 seconds.
2. The nylon composite material according to claim 1, characterized in that: The weight average molecular weight of the polyphenylene ether resin is in the range of 10,000-30,000, preferably 14,000-25,000.
3. The nylon composite material according to claim 2, characterized in that: The weight average molecular weight of the polyphenylene ether resin is in the range of 17000-21000.
4. The nylon composite material according to claim 1, characterized in that: The monomer of the polyphenylene ether resin is 2,6-dimethylphenol.
5. The nylon composite material according to claim 1, characterized in that: The Shore hardness of the polyether polyamide elastomer is D50-D65, and is tested according to ISO 868, with the value recorded after 15 seconds.
6. The nylon composite material according to claim 1, characterized in that: The flame retardant synergist is selected from antimony compounds, and the antimony compound is selected from at least one of antimony trioxide and sodium antimonate.
7. The nylon composite material according to claim 1, characterized in that: The nylon resin is selected from at least one of the polyamide resins selected from aliphatic polyamide resins, semi-aromatic polyamide resins, and polylactamide resins.
8. The nylon composite material according to claim 1, characterized in that: By weight, it also includes 0-40 parts of reinforcing agent, and the reinforcing agent is selected from at least one of glass fiber and mineral filler; by weight, it also includes 0-2 parts of auxiliary agent, and the auxiliary agent is selected from at least one of antioxidant, lubricant and weathering agent.
9. The method for preparing the nylon composite material according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing the components uniformly according to the proportion, extruding and granulating through a twin-screw extruder to obtain a nylon composite material.
10. Use of the nylon composite material according to any one of claims 1 to 8, characterized in that: Used for preparing electronic and electrical parts and parts that require metal inserts.
Citation Information
Patent Citations
A PC / ABS alloy with excellent weld line appearance and high strength and its preparation method
CN105419291B
High-weld bond strength polyethylene / polycarbonate (PE / PC) alloy and preparation method thereof
CN109535682A
Method for removing welding wire in imitation metal effect spraying-free material machining forming
CN110733159A
Polyamide elastomer thermal shrinkable material, polyamide elastomer double-layer material and preparation methods
CN101629015A
Heat conducting nylon plastic and method for preparing same
CN106916443A